Using Interactive Movie to Improve English Foreign Language Learners’ Outcome - Refika Andriani (UIR Press, 2019)
This research aimed at improving the seventh grade students’ vocabulary mastery by using an interactive movie. The method of the research was Classroom Action Research (CAR). The actions were implemented in a cycle with five meetings. In conducting the research, the researcher worked collaboratively with the English teacher. The participants of the research were 30 students of class VII.2 of MTsN 2 Pekanbaru. The instruments used for collecting the data were test, observation checklist, field note, and interview. The findings described that the use of interactive movie was able to improve the students’ vocabulary mastery. After learning by using the interactive movie, the students were able to identify the noun, verb, adjective and adverb related to the topic of descriptive text. It was proved by the quantitative data gotten from the students’ average score of the test. It was 81.06. This score improved significantly from the students’ previous average daily score which was 72. There were several factors influenced the improvement: First, the interactive media was motivated. It can be seen from the teaching and learning process, the students were really enthusiastic in joining all the activities. Second, teaching and learning activity was fun. So, the students enjoy and being active while learning.